1997
DOI: 10.1007/bf03164132
|View full text |Cite
|
Sign up to set email alerts
|

New hole configurations in X-irradiated KTiOPO4 Crystals

Abstract: Electron paramagnetic resonance has been used to study the structure and thermostability of oxygen hole centers produced in KTiOPO 4 (KTP) crystals X-irradiated at 77 K. During the annealing of KTP crystals above 160 K the redistribution of charges took place. Four hole centers were observed at 40 K after the heating of the X-irradiated KTP crystal at different temperatures. The intensity of the hole center 1 decreased and new hole configurations (center 2 and center 3) appeared in the crystals. The g-matrices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
(21 reference statements)
0
7
1
Order By: Relevance
“…Laruhin et al [18] indicate that the observed hyperfine structure in the EPR spectra of this hole center in RTP is most likely due to several of its phosphorus neighbors ( 31 P has I = 1/2 and is 100% abundant). These investigators note that this interpretation of the hyperfine requires principal hyperfine matrix values that differ significantly from the phosphorus values reported for the analogous trapped-hole center in KTP [15,16]. Our present ENDOR spectra, however, show that the phosphorus principal values in RTP are very similar to those in KTP.…”
Section: Introductioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Laruhin et al [18] indicate that the observed hyperfine structure in the EPR spectra of this hole center in RTP is most likely due to several of its phosphorus neighbors ( 31 P has I = 1/2 and is 100% abundant). These investigators note that this interpretation of the hyperfine requires principal hyperfine matrix values that differ significantly from the phosphorus values reported for the analogous trapped-hole center in KTP [15,16]. Our present ENDOR spectra, however, show that the phosphorus principal values in RTP are very similar to those in KTP.…”
Section: Introductioncontrasting
confidence: 71%
“…The g matrix and the hyperfine matrices obtained from the resulting electron paramagnetic resonance (EPR) and electronnuclear double resonance (ENDOR) spectra then verify the existence of an alkali vacancy next to the unpaired spin. Trapped holes located next to potassium vacancies have been observed in KTP crystals [15][16][17], and Laruhin et al [18] have suggested that similar hole centers associated with rubidium vacancies are produced in RTP crystals.…”
Section: Introductionmentioning
confidence: 96%
“…The g-tensors, their principal values and axes for the hole and electron centers for RTP and KTP [10] are presented in Table 1. The g-tensor of the hole center produced by X-irradiation at 77 K in RTP resembles g-tensor of the hole center 1 in KTP [11]. [11,12]).…”
Section: Discussionmentioning
confidence: 99%
“…The g-tensor of the hole center produced by X-irradiation at 77 K in RTP resembles g-tensor of the hole center 1 in KTP [11]. [11,12]). Directions of the largest gvalue principal axes (assigned z) of RTP and KTP crystals are parallel to each other within the uncertainty of 6°.…”
Section: Discussionmentioning
confidence: 99%
“…When a KTP crystal is exposed to ionizing radiation at 77 K (as opposed to room temperature), a large number of "free" holes become trapped on oxygen ions adjacent to potassium vacancies. 34 ' 45 In most KTP crystals, there is a very high concentration of potassium vacancies (much larger than the platinum concentration). Thus, at 77 K, radiation-induced holes are much more likely to be trapped by the potassium vacancies than by the smaller concentration of Pt° ions substituting for K + ions.…”
mentioning
confidence: 99%